An Electrically Actuated Liquid-Metal Gain-Reconfigurable Antenna - George B. Zhang; Ryan C. Gough; Matthew R. Moorefield; Kareem S. Elassy; Aaron T. Ohta; Wayne A. Shiroma (International Journal of Antennas and Propagation)
A tunable liquid-metal antenna demonstrating gain reconfigurability is presented. This antenna uses a reconfigurable stub made with the liquid metal Galinstan. Using continuous electrowetting, a 60 Hz signal with an amplitude of 1 Vpp and 75% duty cycle can actuate the Galinstan continuously along a channel, tuning the stub length and antenna gain. Zero external power is required to maintain the position of the slug. The 5 GHz antenna offers more than 10 dB of analog gain tuning, from −5.90 to 4.43 dB.